Lost and found - Bergen, Lara.; Grant, Mel (New York : Simon Spotlight/Nickelodeon, 2001)
"Uh-oh ... Eliza had been using Debbie's CD player, and now it's missing! In a panic, she asks some South Florida natives--a pelican and an ibis--for help. Then she meets a baby manatee who can't find its mom. Can Eliza help the manatee and still find the CD player before it's too late?"--P. [4] of cover.
"Based on the TV series The wild Thornberrys created by Klasky Csupo, Inc. as seen on Nickelodeon"--T.p. verso.
13
Keywords: Swamp animals -- Florida -- Everglades -- Juvenile fiction; Everglades (Fla.) -- Juvenile fiction; Swamp animals; Lost and found possessions -- Fiction; Sisters -- Fiction; Human-animal communication -- Fiction; Everglades (Fla.) -- Fiction; Florida -- Fiction